2019
DOI: 10.1101/575282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lumen expansion facilitates epiblast-primitive endoderm fate specification in the mouse blastocyst formation

Abstract: Mouse blastocyst formation involves lumen formation and cell fate specification. While many studies have investigated how the blastocyst cell lineages are specified through genetics and signaling, studies into the potential role of the fluid lumen have yet to be conducted. We discover that blastocyst fluid emerges by secretion of cytoplasmic vesicles to intercellular space in addition to trans-epithelial flow. We observe that the beginning of epiblast and primitive endoderm spatial segregation directly follows… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…When the energy of the cavity has accumulated to a certain extent, it may be released and converted in other forms, which affects the entire system. The function of cavity expansion in the lineage specification of PrE/EPI cells has also been observed in a recent study 21 . In our experiments, drug treatment of blastocysts has certain limitations in terms of gene expression, but we are more concerned about changes in physical factors.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…When the energy of the cavity has accumulated to a certain extent, it may be released and converted in other forms, which affects the entire system. The function of cavity expansion in the lineage specification of PrE/EPI cells has also been observed in a recent study 21 . In our experiments, drug treatment of blastocysts has certain limitations in terms of gene expression, but we are more concerned about changes in physical factors.…”
Section: Discussionsupporting
confidence: 64%
“…It has been reported that during the development of blastocysts, PrE precursors move toward the ICM-cavity interface, whereas EPI cells retain inside the ICM compartment 19 . In our experiment, we visualized the migration of PrE precursors from stage E3.5 through time-lapse imaging of PrE-specific single-cell resolution reporter ( Pdgfra H2B-GFP/+ , 20 ) embryos (Figure 1a, b and Supplemental movie S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation